O grau de desenvolvimento rural dos municípios Goianos - Murilo José de Souza Pires; Edilson Gonçalves de Aguiais (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The purpose of this research is to calculate an index of rural development (IDR) to the municipalities of the state of Goiás, in the interregnum census 1996-2000. Therefore, the idea is that the state has a heterogeneous structure in rural areas that coexist with remarkable degree of development areas and, in contrast, others have low dynamism. To achieve the proposed objective at work we used the technical resources of bibliographic and documentary research and adopted the descriptive analytical method. The results show that, in the analyzed period, the state showed generally low level of rural development. However, it is clear that the South-Central region showed the highest values for the IDR in comparison to the North Central region, which demonstrates that the process of modernization of the field more effectively happened in this part of the territory.
Keywords: Q17; 330; development; rural development; Goiás